University Statistical Abstract 1990 (1990)
The University Statistical Abstract (USA) is a collection of informational reports presented in one single source. Serving as a primary planning source document, the USA contains information spanning many University functions: Students, Employees, Budget, Other Resources. The function of this document is to serve the wide-spread informational needs associated with Institutional, College, Division and Unit planning, program review and institutional research. Also called University of North Florida University Statistical Abstract